Sistem Monitoring Online Jaringan Sensor Nirkabel: Survei Kualitas Air dan Udara di Daerah Karawang - Joni Welman Simatupang; Siti Hamidah; Bonifasius Raditya; Fauzi Hadinegara (Fakultas Teknik, 2022)
The existence of industrial development in Karawang regency, can have a very important impact on the surrounding life, namely good or bad impacts. The good impacts include the creation of many jobs, while the bad impacts include pollution of the surrounding environment such as contamination of water and air quality. Therefore, an accurate, reliable, and real-time water and air quality monitoring system is needed. This can be realized by using wireless sensor network technology online. In fact, there was already 1 location (Base Karawang) for air monitoring, while for water monitoring, there were 3 locations: Qua Warungbambu1, Qua Anggadhita, and Qua Kiarapayung. After the authors conducted research by looking for information related to WSN for monitoring water and air conditions in Karawang, followed by a direct survey, it was found that there was already a real-time and centralized monitoring of water and air quality which could be accessed through the Sensync environmental monitoring platform. Monitoring results data in 4 locations show that air still in a good condition and water quality is light polluted, but no harmful effects for human. With easy access to the air and water conditions in Karawang city, which the data is automatically updated every 10 minutes, making the water and air quality will be more easily to know for everyone.